Evaluating the economic roles of Islamic banks in Palestine in financing economic development process between 2006 to 2016 / Mujahed Burhan Kamel Shadid - Mujahed Burhan , Kamel Shadid (2019)
Palestine from a historical point of view is a region inhabited by Arabs of various religious backgrounds such as Judaism, Christianity and Islam. Along with the times of development, the Palestinians are experiencing a tidal wave in which the power of government over it has changed. From an economic point of view, the Palestinian economy is constantly experiencing constraints from financial resources to undergo investment activities in various economic sectors. In this regard, the banking sector is one of the key components of Palestine's economic development. Through it the allocation through this sector can be exploited to finance the development of the Palestinian Economy as a whole. The study aims to examine the economic role played by the Islamic Banking sector that operates in Palestine for the period 2006 to 2016. In order to achieve the objective of the study, analytical descriptive approach is sourced from interviews, annual Islamic banking reports, Financial Reporting Authority of the Palestinian Financial Institutions and Central Bureau Palestine statistics have been applied. The economic role of Islamic banking and Palestinian conventions between 1996 and 2005 was also compared, then analyzed to find out the economic direction of Palestine Islamic Banking during the review period. The findings show that both Islamic banks, Arab Islamic Banks and Palestine Islamic Banks are relatively connected with each other, especially in terms of performance in attracting resources and utilizing financial resources in an appropriate and effective manner. The study also found that Islamic banking capabilities in mobilizing resources and attracting savings are constantly improving. It is shown by the growth rate of Islamic banking resources that remain higher than conventional banking. These resources comprise customer deposits whose average growth rate is doubled from conventional banks. Islamic banking investment deposits are also found to represent two-thirds of total deposits, while this account also covers half of the total investment in conventional banking. Furthermore, from the aspect of Palestinian Islamic banking capability exploiting resources for the purpose of financing economic development, Islamic banking in this study was found to be weak which was proven by the recession in most investments undertaken, reliance on the Murabaha method and direct investment in bank notes with Islamic Foreign banks and directs most of the deviated investments from productive sectors such as agriculture, modern industries and services. Referring to the Palestinian Islamic banking contribution to Gross Domestic Investment, Gross Domestic Product and the provision of direct employment opportunities, Islamic banking is still weak and less contributing. Therefore, this study suggests that both banking institutions will increase their equity. It is also necessary for Islamic banking to create several investment methods that are appropriate to the nature of available resources with an approach that enables these resources to be channeled into sectors such as services, agriculture and modern industries. In addition, the growth and development of Islamic Banking cannot be achieved only through the establishment of branches, but also to the conventional banking transition to Islamic banking.